Industrial design : materials and manufacturing guide. - Lesko, Jim, ....- (Hoboken : Wiley, 2008)
Industrial Design: Materials and Manufacturing Guide, Second Edition provides the detailed coverage of materials and manufacturing processes that industrial designers need without the in-depth and overly technical discussions commonly directed toward engineers. Author Jim Lesko gives you the practical knowledge you need to develop a real-world understanding of materials and processes and make informed choices for industrial design projects. In this book, you will find everything from basic terminology to valuable insights on why certain shapes work best for particular applications. You'll learn how to extract the best performance from all of the most commonly used methods and materials.